Analisis dampak pemberian motivasi melalui lagu nasional terhadap sikap cinta tanah air pada kelas III sekolah dasar - Zoraida Febrianti; Sandra Bayu Kurniawan; Tri Budiharto (Universitas Sebelas Maret, 2022)
This study aims to determine the impact of providing learning motivation through the national song during a limited face-to-face learning period on the attitude of nationalism of students. This research uses descriptive qualitative research methods with a case study approach. The subjects in this study were class III teachers and 31 students in class III. The techniques for collecting data used are interviews, observations, and documentation studies. In testing the validity of the data, the use of technique triangulation and source triangulation. This study used Miles and Huberman's model in the process of data analysis techniques. Based on the results of research, providing motivation through the national songs that are carried out continuously has an impact on the attitude of nationalism of students.